The safety and efficacy of the Stryker OptaBlate™ Bone Tumor Ablation system for vertebral body metastases - Evans, Alexander R.; Harris, Danielle M.; Gumerlock, Mary K.; Shakir, Hakeem J. (Frontiers in Oncology, 2024)
Metastatic spinal lesions are a significant cause of morbidity and decreased quality of life in those with a high tumor burden. Despite treatment modalities such as medical therapy (e.g., chemotherapy, steroids), spinal augmentation procedures, and radiation therapy, many patients still experience refractory back pain due to neoplastic infiltration of the vertebral body and/or pathologic compression fractures. With the aim to address refractory pain in patients who have exhausted conventional treatment options, Stryker developed the OptablateTM Bone Tumor Ablation system (BTA; Stryker Corporation, Kalamazoo, MI), which delivers radiofrequency energy to pathologic vertebral body lesions. In this preliminary single-institution study, we characterize the use of the BTA system in 11 patients undergoing kyphoplasty for pathologic spinal lesions with the goal to demonstrate the impact of this novel technology on refractory pain in this challenging clinical setting.A single-center retrospective chart review was performed on all patients identified as those receiving tumor ablation/kyphoplasty for spinal neoplasms using the OptablateTM BTA system performed by a single surgeon at the University of Oklahoma Medical Center. Sex, age, primary lesion type, presenting symptomatology, spinal level, time of follow-up, and outcome were obtained from the electronic medical record (EMR).Eleven patients (4 males, 7 females) with a mean age of 62 (range, 38-82) years had an average follow-up time of 6 months. Presenting symptoms attributed to spinal pathology included back pain (n = 11, 100%), pathologic fracture (n = 6, 55%), and lower extremity weakness (n = 3, 27%). A total of 20 lesions were ablated at 12 vertebral levels. Eight patients (73%) had improved pain. No complications were reported.This preliminary study documents the safety of the BTA system, in addition to its diverse use across many levels. The majority of patients reported improvement in their pain. Further study is required to fully characterize the use of the BTA system in those with neoplastic spinal pathology.